Investigations of Certain Organ Specific Toxic Effects of Titanium Dioxide Nnanoparticles by In Vivo and In Vitro Methods - Horváth Tamara; Vezér Tünde; Papp András (2019)
The world of nanoparticles (NPs: particles with not more than 100 nm typical diameter at least in one dimension) has gained a great deal of attention in the last ca. 30 years in various fields of research, including life and health sciences. NPs can be cubical or spherical grains, but elongated structures: nano-rods, wires, tubes etc. also exist. This size lends some peculiar characteristics to the NPs, so properties and behavior of the same chemical substance in nano vs. more conventional states can be different. This is due to the high surface-to-volume ratio and to surface reactivity, and leads to biological, including toxicological, interactions not seen with traditional materials, resulting possibly in novel health risks. The relationship between elevated level of ambient airborne NPs and human morbidity and mortality has been generally accepted by now, and particulate air pollution has been recognized as an environmental carcinogenic agent. Among man-made NPs, by-products of various technological procedures, acting as pollutants, and purposefully produced nanomaterials are to be distinguished. Engineered nanomaterials are becoming part of everyday life, in form of NP-containing consumers’ products. The broad spectrum of application with concomitant human exposure raises the question of health risk. Here, a major problem is the lack of toxicity data for most manufactured NPs – and this is why nanotoxicology, an interdisciplinary field related to both environmental hygiene and nanotechnology, emerged. In case of exposure by NPs, the most likely entrance in the (human or animal) organism is, first of all for pollutants, but partly also for nanotechnological NPs, inhalation of air containing a nano-aerosol. NPs, deposited either in the nasopharynx or in the alveoli, are not held back by barriers like the alveolar and capillary wall, and reach other target organs by being phagocyted and transferred along the lymphatic system, or by different mechanisms including transcytosis, and finally are distributed throughout the body via the circulation. In case of consumers’ products, gastrointestinal and dermal uptake may also be of interest. In the aqueous microenvironment of living tissues, surface reactivity of NPs leads to generation of reactive oxygen species (ROS). The resulting oxidative stress can induce damage to biomolecules, primarily lipids and proteins, and finally induce inflammation and/or cytotoxicity. Titanium dioxide (TiO2) is a white, odorless, water insoluble soluble solid of high chemical stability and high melting temperature. It major crystal forms are anatase and rutile. TiO2 as white pigment is used also in the food and pharmaceutical industry. TiO2 NPs of various shapes (grains, rods, wires, tubes) have a broad range of application. Human exposure to TiO2 NPs may occur during manufacturing, processing, and use; in form of aerosols, suspensions or emulsions. The most health relevant routes of exposure in workplaces are inhalation and dermal exposure, while non-occupational exposure is most likely dermal or oral. Ill effects – increased oxidative stress, inflammation, lung damage – due to airborne TiO2 in humans suffering occupational exposure have been in fact documented and successfully modeled in animals. Nervous system effects would also be expected for an agent able to cross the blood-brain barrier and to cause oxidative stress. However, human data to this point are scarce. Animal experiments, done predominantly in mice and less in rats, showed various central nervous alterations including cell damage, altered synaptic transmission and plasticity, memory impairment and increased anxiety. Other organs, including the kidneys, also showed signs of damage – activation of inflammatory mediators, histological damage, decreased function – in rats and mice on TiO2 NP administration. These effects could be deduced to cellular uptake of nano-TiO2, followed by ROS generation, engulfment by lysosomes, and release of enzymes from the latter initiating inflammation and cell death. Exposure of humans to TiO2 NPs can take place both in occupational settings, in the residential environment, or during free-time activities, and certain properties of the TiO2 NPs suggest harmful effects on various organs and organ systems of humans or animals but the available reports on such effects are not yet conclusive. Based on the experience gained at the Department of Public Health in examining the toxicity of metal oxide NPs for over 10 years, and on the properties and possible effects of TiO2 NPs outlined above, it was decided to investigate in the present PhD work the alterations evoked by TiO2 NPs with a complex approach...
A nanorészecskék világa az utóbbi 30 évben nagy figyelmet kapott különböző kutatási területeken, így az élet- és egészségtudományok terén is. Nanopartikulumnak (NP) az általánosan elfogadott definíció szerint a legalább egyik dimenzióban 100 nm tipikus kiterjedésnél nem nagyobb részecskéket tekintjük. Ezek nemcsak gömb- vagy köbszerűek lehetnek, hanem megnyúlt formájúak is: nanopálcikák, -szálak, -csövek, sőt nagyobb méretű objektumok nanoméretű felületi mintázata is ismert. Kis méretük, nagy felület-térfogat arányuk, és felületi reakciókészségük miatt a NP-oknak több sajátos jellemzőjük van. Ugyanaz a vegyület szokványosabb ill. nano-állapotban eltérő tulajdonságokat és viselkedést mutathat, amiből a hagyományos anyagok esetében nem ismert biológiai, azon belül toxikológiai kölcsönhatások, végső soron újszerű egészségi kockázatok eredhetnek. A környezeti levegő magasabb NP-tartalma, illetve az emberi megbetegedések és halálozások közötti összefüggés mára általánosan elfogadottá vált. A (nanorészecskéket is magában foglaló) aeroszol-koncentráció a környezeti levegőminőség fontos mutatója. A NP-ok oki szerepét többféle nem-fertőző betegségben (asztma, COPD, szívbetegségek) számosan elemezték, a partikuláris légszennyezés pedig elismert környezeti rákkeltő tényezővé vált. Az emberi eredetű NP-ok között megkülönböztetjük a melléktermékeket és szennyezőket, illetőleg a szándékosan előállított nanotechnológiai anyagokat. Fogyasztási cikkekben megjelenve a nanoanyagok a mindennapi élet részeivé is válnak. A széles alkalmazási terület és a velejáró emberi kitettség felveti az egészségi kockázat kérdését; a gyártott nanoanyagok többségéről azonban nincs elegendő toxicitási adat, ezért mára a nanotoxikológia, mint a környezet-higiénével és nanotechnológiával is kapcsolatos interdiszciplináris terület, fontos kutatási témává vált. A NP-okkal történő expozíció (elsősorban szennyezők esetén, de részben nanotechnológiai anyagoknál is) legvalószínűb a nano-aeroszolt tartalmazó levegő belégzése által. Az orrgaratban vagy az alveolusokban lerakódott NP-okat a határfelületek nem állítják meg, így a részecskék más célszerveket is elérhetnek:.fagocitálódva a nyirokrendszerben haladhatnak, transzcitózissal átléphetnek hámrétegeken, végül a keringésbe jutva a teljes szervezetben szétszóródnak. Fogyasztási cikkekből bőrön és az emésztőcsatornán át is felszívódhatnak. Az élő szövetek vizes miliőjében a NP-ok felületi reakciókészsége reaktív oxigén-származékok (ROS) keletkezését indítja meg. A létrejövő oxidatív stressz károsítja a biomolekulákat, főleg lipideket és fehérjéket, és végül gyulladáshoz vagy sejtpusztuláshoz vezető folyamatokat indít be. A titán-dioxid (TiO2) fehér, szagtalan, vízoldhatatlan, kémiailag igen stabil, magas olvadáspontú vegyület. Két fő kristályformája az anatáz és a rutil. Fehér pigment formájában használatos az élelmiszer- és gyógyszeriparban is. Változatos alakú (szemcse, pálcika, szál, cső) TiO2 NP-ok sokféle alkalmazásban fordulnak elő. Emberi expozíció a TiO2 NP-ok gyártása, feldolgozása és alkalmazása során, aeroszol, szuszpenzió ill. emulzió formájában történhet. A munkahelyi egészség szempontjából az inhalációs és dermális expozíció a jelentős, míg a nem-foglalkozási expozíció leginkább bőrön és szájon át történhet. A munkahelyi nano-TiO2 kitettségből származó egészségi ártalom – fokozott oxidatív stressz, gyulladás, tüdőkárosodás – ismert, és állatokban már modellezett, jelenség. A nano-TiO2 humán idegrendszeri hatásairól igen kevés az adat. Állatkísérletben – főleg egéren, kevésbé patkányon – a központi idegrendszerben többféle eltérést mutattak ki: sejtkárosodást, a szinaptikus átvitel és plaszticitás, a transzmitter-forgalom megváltozását, károsodott memóriát, fokozott szorongást. Más szervekben, így a vesékben is kimutatták az ártalom jeleit: gyulladás-mediátorok aktiválódását, szöveti károsodást, csökkent működést. E hatások a nano-TiO2 sejtekbe kerülésére vezethetők vissza, amit ROS keletkezése, a NP-ok lizoszómákba kerülése, és azokból gyulladást és sejthalált beindító enzimek felszabadulása követ. Emberi NP-expozíció bekövetkezhet munkahelyen, lakókörnyezetben, szabadidős tevékenységek során. Egyes tulajdonságaik által a TiO2 NP-ok szervek és szervrendszerek károsodását idézhetik elő az emberi és állati szervezetben, az ilyen hatásokat leíró közlemények azonban végkövetkeztetést még nem tesznek lehetővé. A Népegészségtani Intézetben több mint 10 éve folyik a fémoxid nanorészecskék toxicitásának vizsgálata. Erre, valamint TiO2 NP-ok tulajdonságaira és lehetséges hatásaira alapozva, jelen PhD munkában a TiO2 NP-ok által kiváltott elváltozások komplex megközelítésű vizsgálatát tűztük ki célul...
Disszertacio
Keywords: elméleti orvostudományok; Általános orvostudomány